Planning Network of Sports Facilities in the Context of Montenegro Case Study: Herceg-Novi, Podgorica and Danilovgrad - Svetislav G. Popović; Jelena Bajić Šestović; Nevena Đurović Mašanović; Sanja Vlahović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2016)
Sports facilities of a city through the a long history of development of the city, starting with ancient Greece and Rome, had been evermore recognized as important areas of the city, the place of communication and interaction between people, places of unwinding everyday social life, so-called point of the urban gatherings. In addition to the social aspect, facilities for sport are often involved in the formation of the visual identity of a city. The land intended for sport and recreation are areas which are in the planning document designed to develop sports and recreational facilities, outdoors or indoors. Globalisation and the transition effects in Montenegro contributed faster transformation of society. This paper explores the urban parameters for the planning of sports and recreational zones in the city. During the transition period, the last 25 years, the system of planning and land management has experienced a major transformation in terms improper planning development of sports facilities, not supporting sports and recreation needs of the residents. For central and coastal region of Montenegro, it is characteristic rapid urbanization with significant migration and dominant construction of residential blocks and tourist facilities on the coast. The planning area for residential, has not been accompanied by adequate network of sports facilities. The purpose of this paper is to determine whether the existing network of sports facilities in Herceg-Novi, Danilovgrad and Podgorica can meet the needs of the residents, as well as to provide recommendations for the further development of the network of sports facilities.